Farm costs and benefits of antimicrobial use reduction on broiler farms in Dar es Salaam, Tanzania - Azabo, Rogers R.; George, Janeth I.; Mshana, Stephen E.; Matee, Mecky I.; Kimera, Sharadhuli I. (Frontiers in Antibiotics, 2022)
Of all animal derived-food, the demand for poultry meat increases the most dynamically. The poultry sector can only satisfy this demand by introducing intensive production where antimicrobial use is inevitable. In intensive animal husbandry, the prevention and control of bacterial infections is an important factor in production. Antimicrobial use is an effective and relatively cheap measure to prevent and control infections and maintain animal health and productivity. The aim of this study was to get insight into the costs and benefits of different scenarios for the reduction of antimicrobial use at broiler farms in Dar es Salaam, Tanzania. The research focused on economic consequences for the average farmer. The economic costs and benefits of different scenarios and levels of antibiotic reduction were estimated by partial budgeting using the Mclnerney (1996) Model. The disease cost of the current situation was US225. On reduction of antimicrobial use by 20% the avoidable disease cost was US 31, by 50% was US 83 and by 100% was US 147. In conclusion, according to the model, a reduction in antibiotic use will increase production costs. Reducing antibiotic use can therefore only be accomplished when there is a good alternative to prevent and control diseases. Future research on antibiotic reduction’s effect on mortality and morbidity is needed to improve the model. Furthermore, research on the development and efficiency of additional management measures and other methods to produce poultry meat without high levels of antibiotics is needed.